2018
DOI: 10.1152/physrev.00013.2017
|View full text |Cite
|
Sign up to set email alerts
|

Human Olfactory Receptors: Novel Cellular Functions Outside of the Nose

Abstract: Olfactory receptors (ORs) are not exclusively expressed in the olfactory sensory neurons; they are also observed outside of the olfactory system in all other human tissues tested to date, including the testis, lung, intestine, skin, heart, and blood. Within these tissues, certain ORs have been determined to be exclusively expressed in only one tissue, whereas other ORs are more widely distributed in many different tissues throughout the human body. For most of the ectopically expressed ORs, limited data are av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
146
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(154 citation statements)
references
References 206 publications
(479 reference statements)
1
146
1
6
Order By: Relevance
“…N-term, 7-TMs, 3-ECLs, 3-ICLs and C-term defined in the structure-based MSA in Figure 1), revealed that 65% of the mutations were located in the TM regions (50,703 missense, 20,296 synonymous, 3,170 frameshifts and 1,657 stop gained variants) ( Figure 5). TM6 accumulates more changes (13,117 variants), followed by TM3 (12,782) and ECL2 (11,057 The analysis of individual positions within the conserved GPCR topological domains, using the BW nomenclature, reveals that, overall, the occurrence of natural variants is not restricted to a specific TM region or particular location, with an average of 360 changes per site ( Figure 6). However, position 3.50 (995 total variations, 816 missense) stand out from the rest of sites ( Figure 6C).…”
Section: Topological Assignment To Sequence Variantsmentioning
confidence: 99%
See 2 more Smart Citations
“…N-term, 7-TMs, 3-ECLs, 3-ICLs and C-term defined in the structure-based MSA in Figure 1), revealed that 65% of the mutations were located in the TM regions (50,703 missense, 20,296 synonymous, 3,170 frameshifts and 1,657 stop gained variants) ( Figure 5). TM6 accumulates more changes (13,117 variants), followed by TM3 (12,782) and ECL2 (11,057 The analysis of individual positions within the conserved GPCR topological domains, using the BW nomenclature, reveals that, overall, the occurrence of natural variants is not restricted to a specific TM region or particular location, with an average of 360 changes per site ( Figure 6). However, position 3.50 (995 total variations, 816 missense) stand out from the rest of sites ( Figure 6C).…”
Section: Topological Assignment To Sequence Variantsmentioning
confidence: 99%
“…ORs are characterized by intronless coding regions of average length of 310 codons (~1kb) and constitute the largest multigene family in humans, with a functional gene repertoire estimated between 322 and 390 genes, divided into two main classes, 17 families and more than 150 subfamilies [7]. This broad array of receptors, like in other terrestrial mammals, is shared with tetrapods (families [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and marine vertebrates (families 51-56) [8], and seems necessary to respond efficiently to the extraordinary chemical diversity of odorants in Earth's ecosystems [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olfactory receptors (OR) are G-protein coupled receptors for detecting smell sensation (Schild and Restrepo 1998). Although ORs are originally described in olfactory neurons, emerging evidence suggest that some ORs are also expressed in other tissues (Maßberg and Hatt 2018). Chang et al reported high abundance of Olfr 78 (also known as MOL2.3 and MOR 18-2) gene expression in glomus cells of the mouse carotid body (Chang et al 2015), a finding that was subsequently confirmed using single cell mRNA analysis in neonatal mice (Zhou et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Another example is the olfactory receptor family, which were discovered in 1991 in sensory neurons and are composed of about 400 genes in humans. Olfactory receptors have been shown to be expressed in many non-sensory tissues in both development and adult tissues including the gastrointestinal system (Maßberg & Hatt, 2018). However, we have little understanding of their functions in these contexts.…”
Section: Introductionmentioning
confidence: 99%